2018
DOI: 10.1093/jas/sky194
|View full text |Cite
|
Sign up to set email alerts
|

Influence of feeding direct-fed microbial supplementation on growth performance and feeding behavior in naturally fed and conventionally fed finishing cattle with different dietary adaptation periods

Abstract: To determine the effects of finishing system (conventional vs. natural), dietary adaptation length (14 vs. 28 d), and direct-fed microbial (DFM) supplementation (no DFM vs. DFM) on growth performance and feeding behavior, 120 yearling steers (390 ± 2.8 kg) were used in a completely randomized design with a 2 × 2 × 2 factorial arrangement of treatments. Feed intake was monitored using the Insentec feeding system. Blood samples were collected every 28 d. After 140 d on feed, steers were slaughtered and carcass c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
(28 reference statements)
1
3
0
Order By: Relevance
“…(2003) frequently reported the literature supports that direct-fed microbial supplementation is not likely to affect carcass traits. Others have also reported findings similar to those in the present experiment; Swanson et al. (2018) evaluated the effects of the finishing system, dietary adaption length, and direct-fed microbial supplementation on the growth performance and feeding behavior of feedlot steers but did not report an effect of the direct-fed microbial on carcass characteristics.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…(2003) frequently reported the literature supports that direct-fed microbial supplementation is not likely to affect carcass traits. Others have also reported findings similar to those in the present experiment; Swanson et al. (2018) evaluated the effects of the finishing system, dietary adaption length, and direct-fed microbial supplementation on the growth performance and feeding behavior of feedlot steers but did not report an effect of the direct-fed microbial on carcass characteristics.…”
Section: Resultssupporting
confidence: 81%
“…Incorporating nutraceuticals into diets of feedlot cattle, especially during the receiving period, may be advantageous, particularly as a management tool to aid in improving animal performance and decreasing morbidity ( Duff and Galyean, 2007 ; Ballou et al., 2019 ;). Research also suggests the supplementation of nutraceuticals in diets of newly received cattle may have the potential to decrease the dietary adaption period, allowing cattle to consume a more energy-dense diet earlier in the finishing period ( Swanson et al., 2018 ). Finally, some data suggest that feeding nutraceuticals may increase performance of finishing cattle ( NASEM, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Swanson et al (2018) reported that an adaptation period of two weeks or four weeks had little effect on growth performance (e.g., final body weight and average daily gain). However, slight risks were present for feedlot steers with an adaptation period of less than four weeks, mainly for animals suffering from subacute or acute acidosis [38]. Previous methodological research has found that an adaptation period of 14 days was suitable for changeover and crossover nutritional experiments with cattle fed forage-based diets [13].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, alterations in the rate of DMI and time eating by steers supplemented with RAC could potentially influence rumen fermentation and result in decreased ruminal pH ( Gonzalez et al, 2012 ). Although visual signs of acidosis were not observed in steers from either treatment, changes in forage source and level ( Swanson et al, 2017 ), grain source ( Rodenhuis et al, 2017 ) and processing ( Swanson et al, 2014 ), time of feeding ( Prezotto et al, 2017 ), and feed additive inclusion ( Swanson et al, 2018 ) can potentially alter effects and interactions with RAC.…”
Section: Discussionmentioning
confidence: 99%